INJURIES INCIDENCE IN BRAZILIAN PRO TRIATHLETES (Fiep Bulletin - online, 2014)
The International Triathlon Union (ITU) defines triathlon as a modality composed by swimming in open waters, cycling in streets or roads and running. The sport became popular and, every day, more people adhere to the practice of triathlon and have to overcome obstacles when swimming, cycling and running in order to reach the finish line in a competition. This study aimed to identify the injuries incidence in Brazilian professional triathletes. The study was characterized as descriptive and the sample was composed by eighteen athletes (14 male and 4 female). Six of them were members of the Brazilian National Team in 2003 and champions of the Santa Catarina State Cup of Triathlon, also in 2003. The instrument of the study was a validated questionnaire composed by items that supplied information about the incidence, the type and the reason of the injury; the body region where the injury occurred; and the type of injury treatment. One observed that from the 18 athletes, 13 (72,2%) had already suffered some injury and 5 (27,8%) had never suffered any kind of injury. The results of this study accord to the results reported in the literature, regarding the type of injury and the body region where the injury occurred. Considering the type of injury, the muscular one was the most cited by the subjects. The body region most affected was the knee and the most cited reason for the injury was the overtraining. As the injuries most occur during the training sessions and not during the competitions one suggest that coaches and athletes should look for preventive actions in order to avoid the overtraining and the incidence of injuries, as stretching every day as part of the daily routine, improving the performance of these young Brazilian triathletes.
Keywords: triathlon; injuries; training